Bacillus: A Biological Tool for Crop Improvement through Bio-Molecular Changes in Adverse Environments - Radhakrishnan, Ramalingam; Hashem, Abeer; Abd_Allah, Elsayed F. (Frontiers in Physiology, 2017)
Crop productivity is affected by environmental and genetic factors. Microbes that are beneficial to plants are used to enhance the crop yield and are alternatives to chemical fertilizers and pesticides. Pseudomonas and Bacillus species are the predominant plant growth-promoting bacteria. The spore-forming ability of Bacillus is distinguished from that of Pseudomonas, and members of this genus also survive for a long time under unfavorable environmental conditions. Bacillus spp. secrete several metabolites that trigger plant growth and prevent pathogen infection. Limited studies have been conducted to understand the physiological changes that occur in crops in response to Bacillus spp. to provide protection against adverse environmental conditions. This review describes the current understanding of Bacillus-induced physiological changes in plants as an adaptation to abiotic and biotic stresses. During water scarcity, salinity and heavy metal accumulate in soil, and Bacillus spp. produce exopolysaccharides and siderophores, which prevent the movement of toxic ions and adjust the ionic balance and water transport in plant tissues while controlling the pathogenic microbial population. In addition, the synthesis of indole-3-acetic acid, gibberellic acid and 1-aminocyclopropane-1-carboxylate (ACC) deaminase by Bacillus regulates the intracellular phytohormone metabolism and increases plant stress tolerance. Cell-wall-degrading substances, such as chitosanase, protease, cellulase, glucanase, lipopeptides and hydrogen cyanide, from Bacillus spp. damage the pathogenic bacteria, fungi, nematodes, viruses and pests to control their populations in plants and agricultural lands. The normal plant metabolism is affected by unfavorable environmental stimuli, which suppress crop growth and yield. Abiotic and biotic stress factors that have detrimental effects on crops are mitigated by Bacillus-induced physiological changes, including the regulation of water transport, nutrient up-take and the activation of the antioxidant and defense systems. Bacillus association stimulates plant immunity against stresses by altering stress-responsive genes, proteins, phytohormones and related metabolites. This review describes the beneficial effect of Bacillus spp. on crop plants, which improves plant productivity under unfavorable climatic conditions, and the current understanding of the mitigation mechanism of Bacillus spp. in stress-tolerant and/or stress-resistant plants.